2022
DOI: 10.1007/s10566-022-09683-z
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Learning Mind (HLM): Cluster Randomized Controlled Trial on A Mindfulness Intervention, Moderators and Association with Perceived Socioeconomic Status, and Comparison to Other National Data

Abstract: Background This paper presents the baseline characteristics and their moderators in the Healthy Learning Mind (HLM)– school-based cluster-randomized controlled trial. Objectives The paper evaluates the state of various measures of well-being, their moderators and how these results compare to national and global norms/population studies. Methods Data were collected from all participants prior to the intervention and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Interestingly, the study revealed that being more financially literate does not necessarily improve perceived economic well-being.The variable of PSES covered a wide-range of studies. Most of previous studies discussed about PSES in correlation with psychological and social issues, such as about people behavior [17], healthy learning mind [18], and financial literacy but more into perceived economic outcomes [16].…”
Section: Perceived Socio-economic Statusmentioning
confidence: 99%
“…Interestingly, the study revealed that being more financially literate does not necessarily improve perceived economic well-being.The variable of PSES covered a wide-range of studies. Most of previous studies discussed about PSES in correlation with psychological and social issues, such as about people behavior [17], healthy learning mind [18], and financial literacy but more into perceived economic outcomes [16].…”
Section: Perceived Socio-economic Statusmentioning
confidence: 99%
“…It prepares them for the transition to secondary school in grade five, when children start to follow different tracks (i.e., different types of school) in the German stratified school system. Because the SES of children’s families seems to moderate the effects of mindfulness interventions (Lassander et al, 2022 ), their parents’ education was included as a background variable. The current study evaluated the effects of the teacher-led Breathing Break Intervention on children’s prosocial behavior and their perceptions of the social classroom climate in a RCT with an ACG and age, gender, and parental education as covariates.…”
mentioning
confidence: 99%